(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article examines the issue of using an effective teaching system in teaching physics. The importance of didactic methods in this regard is revealed. Particular attention is paid to the effectiveness of integration with other disciplines in the field of in-depth study of physics.